Rapid investigation of cases and clusters of Legionnaires' disease in England and Wales using direct molecular typing - Mentasti, Massimo; Afshar, Baharak; Collins, Samuel; Walker, Jimmy; Harrison, Timothy G.; Chalker, Vicki (Journal of medical microbiology, 2016)
Legionella pneumophila is the leading cause of Legionnaires' disease, a severe pneumonia that can occur as sporadic cases or point-source outbreaks affecting multiple patients. The infection is acquired by inhalation of aerosols from contaminated water systems. In order to identify the probable source and prevent further cases, clinical and environmental isolates are compared using phenotypic and genotypic methods. Typically up to 10 days are required to isolate L. pneumophila prior to the application of standard typing protocols. A rapid protocol using a real-time PCR specific for L. pneumophila and serogroup 1, combined with nested direct molecular typing, was adopted by Public Health England in 2012 to reduce reporting time for preliminary typing results. This rapid protocol was first used to investigate an outbreak that occurred in July/August 2012 and due to the positive feedback from that investigation, it was subsequently applied to other incidents in England and Wales where faster typing results would have aided incident investigation. We present here results from seven incidents that occurred between July 2012 and June 2015 where the use of this rapid approach provided preliminary characterization of the infecting strain in an average 1.58 days (SD 1.01) after sample receipt in contrast to 9.53 days (SD 3.73) when standard protocols were applied.